Preparation and bactericidal effect of composites based on crosslinked copolymers containing silver nanoparticles - Maria, Luiz C. de S.; Oliveira, Rachel O.; Merçon, Fabio; Borges, Maria E. R. S. P.; Barud, Hernane S. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Messaddeq, Younes [UNESP]; Wang, Shu H. (Associação Brasileira de Polímeros, 2010)
Commercial copolymers based on styrene and divinylbenzene containing sulfonic acid groups were used as support for the incorporation of silver nanoparticles. These nanoparticles were obtained in situ by the reduction of Ag+ by using hydroxylamine in the presence of a protective agent. These materials were characterized with determination of the silver content and their morphological characteristics. The antibacterial activity of the final products against Escherichia coli was evaluated and the results show that the synthesized copolymers had antibacterial effect varying from 54 to 100%. The most efficient composite was made with small, well distributed particles.
Keywords: Nanocomposite; silver; copolymer; resin